2013
DOI: 10.1371/journal.pone.0054254
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes and Patterns of Antibiotic Resistance in Strains Causing Invasive Pneumococcal Disease in Children Less than 5 Years of Age

Abstract: ObjectiveThe serotypes and patterns of antibiotic resistance of Streptococcus pneumoniae (S. pneumoniae) strains that cause invasive pneumococcal disease (IPD) in infants were analyzed to provide guidance for clinical disease prevention and treatment.MethodsThe clinical features of confirmed IPD were evaluated in 61 patients, less than 5 years of age, who were admitted to our hospital between January 2009 and December 2011. The serotypes and antibiotic resistance of strains of S.pneumoniae were determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 14 publications
(23 reference statements)
5
26
0
Order By: Relevance
“…This is largely akin to our previous findings for isolates from patients suffering from CAP [14] as well as data from other countries in Europe [26] and the Far East [27,28]. Thus, determination of the prevalent STs/SGs in patients may help in fine-tuning therapy by avoiding the use of antibiotics known to be poorly effective.…”
Section: Discussionsupporting
confidence: 79%
“…This is largely akin to our previous findings for isolates from patients suffering from CAP [14] as well as data from other countries in Europe [26] and the Far East [27,28]. Thus, determination of the prevalent STs/SGs in patients may help in fine-tuning therapy by avoiding the use of antibiotics known to be poorly effective.…”
Section: Discussionsupporting
confidence: 79%
“…In China, antibiotics misuse is pervasive [6,7], leading to very high and growing rates of AMR in both hospital and community-acquired infections [8–10]. A review of antibiotic use in China demonstrated that 80% of inpatients and 50.3% of outpatients were prescribed with antibiotics, and as many as 75% of patients with seasonal influenza were treated with antibiotics [11].…”
Section: Introductionmentioning
confidence: 99%
“…In China over prescribing of antibiotics is highly pervasive [5,6]. This has led to very high and increasing rates of AMR in both hospital and community-acquired infections [7][8][9]. With one-fifth of the world's population living in China, this is a serious global concern.…”
Section: Introductionmentioning
confidence: 99%